Distribution of Ability Eleocharis dulcis to Adsorb Heavy Metals in Roots, Stems and Leaves - Mazidah, Mazidah; Suheryanto, Suheryanto; Sarno, Sarno (Program Pascasarjana Universitas Sriwijaya, 2025)
Heavy metal pollution, including lead (Pb), zinc (Zn), and copper (Cu) in swamp environments, is increasing and poses a significant threat to ecosystem integrity and human health. This study aims to evaluate the phytoremediation potential of Eleocharis dulcis in accumulating heavy metals in root, stem, and leaf tissues. The experimental method involved growing Eleocharis dulcis for 20 days in media artificially contaminated with Pb, Zn, and Cu metals at concentrations of 5, 10, and 15 ppm. Observations were made on metal accumulation in plant tissues on days 5, 10, 15, and 20. The results showed that concentration and duration of exposure significantly influenced the pattern of metal accumulation. The highest accumulations were recorded in leaf tissue, specifically Pb at 87.527 mg/kg, Zn at 32.93 mg/kg, and Cu at 43.522 mg/kg. These findings indicate that Eleocharis dulcis has selective metal uptake and translocation mechanisms and high tolerance to heavy metal stress, and has the potential to be an effective phytoremediation agent for the rehabilitation of heavy metal-contaminated wetlands and support sustainable environmental management.